Is lack of standardization impacting the consumer IoT market - Kalliovaara, Joakim (My University, 2022)
Abstract IoT has been trending especially during the past decade. The market is growing in a rapid pace, but since it is such a dynamic field, regulation cannot fully keep up with the technical development. How development is done, how products are priced, and de- vices interoperate with each other in a shared network of things have included a lot of freedom from the market supplier point of view. This thesis will investigate the market with a qualitive research perspective with the support of existing literature and by interviewing IoT professionals. The IoT field is constantly changing, therefore having recent publications supporting the research can be considered important. Due to the complexity of the topic, interviewing a handful of IoT professionals was chosen to be the empirical approach for the thesis. The aim for this research is to estimate if the IoT market is lacking standardization and narrowing the impact of that towards the consumer. The standardization doesn’t al- ways need to be based on regulation, but as an example GDPR has brought stand- ardization in the data visibility in IoT. There are just that many areas in IoT which could include standardization and GDPR is only the tip of the iceberg. With the case exam- ples including the analysis on how it affects the consumers, this thesis can be used as a source of ideas to analyze areas of IoT that could be standardized, especially if the standardization is aiming to better the market position of the weaker party, the con- sumer.

Tiivistelmä IoT on trendannut etenkin viimeisen vuosikymmen aikana. Sen markkina kasvaa kovaa vauhtia, mutta markkinan dynaamisesta luonteesta johtuen regulaatio ei täysin kykene pysymään kehityksen perässä. Miten kehitystä harjoitetaan, miten tuotteita hinnoitellaan ja miten laitteet kommunikoivat keskenään on sisältänyt palveluntarjoajan näkökulmasta paljon vapauksia. Tämä Pro gradu tutkii kyseistä markkinaa kvalitatiivisin tutkimustavoin tukeutuen kirjallisuuteen aiheesta ja haastattelemalla alan ammattilaisia. IoT:n muuttuvan luonteen takia, kirjallisuudessa on pyritty suosimaan mahdollisimman uusia julkaisuja. Aiheen kompleksisuudesta johtuen taas haastatteluihin pyrittiin löytämään henkilöitä, joilla oli mahdollisimman kattavaa ymmärrystä ja kokemusta sen parista. Tämän tutkimuksen tavoitteena on tutkia standardoimattomuuden puutetta IoT-markkinalla ja keskittyä etenkin sen vaikutuksiin kuluttajiin. Standardoinnin ei tarvitse aina liittyä regulaatioon, mutta hyvänä esimerkkinä standardoinnin lisäämisestä IoT-markkinoilla toimii GDPR. Esimerkkitapausten kautta, miten standardoinnin puute vaikuttaa markkinaan ja kuluttajiin, tämä tutkielma pyrkii tuomaan esille ideoita mihin tulevaa mahdollista standardointia markkinalla voisi kohdistaa, etenkin mikäli standardoinnilla pyritään vaikuttamaan kuluttajan asemaan markkinalla.
Keywords: IoT, Standardization, Consumer IoT, Interoperability